Tetrahymena thermophila glutathione-S-transferase superfamily: an eco-paralogs gene network differentially responding to various environmental abiotic stressors and an update on this gene family in ciliates - Ortega, Ruth; Martin-González, Ana; Gutiérrez, Juan-Carlos (Frontiers in Genetics, 2025)
Glutathione S-transferases constitute a superfamily of enzymes involved mainly, but not exclusively, in the detoxification of xenobiotic compounds that are considered environmental pollutants. In this work, an updated analysis of putative cytosolic glutathione S-transferases (cGST) from ciliate protozoa is performed although this analysis is mainly focused on Tetrahymena thermophila. Among ciliates, the genus Tetrahymena has the highest number (58 on average) of cGST genes. As in mammals, the Mu class of cGST is present in all analyzed ciliates and is the majority class in Tetrahymena species. After an analysis of the occurrence of GST domains in T. thermophila, out of the 54 GSTs previously considered to be Mu class, six of them have been discarded as they do not have recognizable GST domains. In addition, there is one GST species-specific and another GST-EF1G (elongation factor 1 gamma). A structural analysis of T. thermophila GSTs has shown a wide variety of β-sheets/α-helix patterns, one of the most abundant being the canonical thioredoxin-folding pattern. Within the categories of bZIP and C4 zinc finger transcription factors, potential binding sites for c-Jun and c-Fos are abundant (32% as average), along with GATA-1 (71% average) in the T. thermophila GST gene promoters. The alignment of all MAPEG (Membrane Associated Proteins involved in Eicosanoid and Glutathione metabolism) GST protein sequences from Tetrahymena species shows that this family is divided into two well-defined clans. The phylogenetic analysis of T. thermophila GSTs has shown that a cluster of 19 Mu-class GST genes are phylogenetic predecessors of members from the omega, theta and zeta classes. This means that the current GST phylogenetic model needs to be modified. Sixteen T. thermophila GST genes, together with two clusters including three genes each with very high identity, have been selected for qRT-PCR analysis under stress from eleven different environmental stressors. This analysis has revealed that there are GST genes that respond selectively and/or differentially to each stressor, independently of the GST class to which it belongs. Most of them respond to the two more toxic metal(loid)s used (Cd or As).